Type 2 Diabetes Mellitus Provokes Rat Immune Cells Recruitment into the Pulmonary Niche by Up-regulation of Endothelial Adhesion Molecules - Eghbal Zarafshan; Reza Rahbarghazi; Jafar Rezaie; Mohammad Reza Aslani; Shirin Saberianpour; Mahdi Ahmadi; Rana Keyhanmanesh (Tabriz University of Medical Sciences, 2022)
Purpose: Diabetes mellitus, especially type 2, is conceived as a devastating chronic metabolic disease globally. Due to the existence of an extensive vascular network in the pulmonary tissue, it is suggested that lungs are sensitive to the diabetic condition like other tissues. This study was designed to address the possible effect of type 2 diabetes mellitus on the promotion of pathological changes via vascular injury. Methods: Sixteen male Wistar rats were randomly allocated to the two of Control and T2D groups. To induce type 2 diabetes, rats were received high-fat and a single dose of STZ. On week 12, rats were euthanized and lungs samples were taken. Using Hematoxylin and Eosin staining, the pathological changes were monitored. The expression of vascular ICAM-1 and VCAM-1, and IL-10 was monitored using real-time PCR assay. The level of TNF-α was detected using ELISA assay. Nitrosative stress was monitored using the Griess assay. Results Pathological examination in bronchoalveolar discharge revealed the existence of mild to moderate interstitial bronchopneumonia and increased neutrophilic leukocytosis compared to the control. Enhanced ICAM-1 and VCAM-1 expression and suppression of IL-10 was found using real-time PCR analysis (p<0.05). The levels of TNF-α and NO were increased with diabetic changes compared to the control rats (p<0.05). Conclusion T2D could promote pulmonary tissue injury via the production of TNF-α and up-regulation of vascular ICAM-1 and VCAM-1. The inflammatory status and vascular ICAM-1 and VCAM-1 increase immune cell recruitment into the pulmonary niche.